Interesting response to ventricular overdrive pacing during regular narrow QRS tachycardia. What is the mechanism? - Mohanan Nair, Krishna Kumar (Indian Pacing Electrophysiol J, 2019)
33 year old gentleman has undergone an electrophysiology study for recurrent paroxysmal palpitation. During one of the episodes of palpitation a regular narrow QRS tachycardia was documented which has terminated with intravenous adenosine. Baseline electrocardiogram did not show any pre-excitation. Atrial-His (AH) and His-Ventricular (HV) intervals were normal at baseline. There was no evidence of dual atrioventricular (AV) nodal physiology. Earliest atrial electrogram during ventricular pacing was recorded at coronary sinus (CS) 9,10 dipoles placed at CS OS region. Narrow QRS tachycardia with cycle length (TCL) of 400 ms and earliest retrograde atrial activation at CS 9,10 dipoles was induced with programmed ventricular stimulation. Ventricular overdrive (VOD) pacing was performed at 30 ms shorter than TCL during the tachycardia (Fig: 1). What is the mechanism of tachycardia?